A study on the translation of english property insurance contracts into vietnamese - Trịnh,Xuân Thắng (ĐHĐN., 2015)
There is a growing demand about the translation of English property insurance contracts into Vietnamese, especially when many foreign companies are in business in Vietnam. Therefore, how to translate an English property insurance contract into Vietnamese effectively should be paid considerable attention. However, this is not an easy task because most of translators are not the experts who have specialized knowledge of insurance.. The findings show that communicative method is the most suitable method used when translating English property insurance contracts into Vietnamese. Translators need apply many different translation procedures such as shift or transposition, modulation, paraphrase, expansion to translate English property insurance contracts into Vietnamese. The findings also show some linguistic features and syntactic features that cause difficulties for translators including archaic words, borrowed words, long sentences and declarative sentences. In addition, word choice and cultural differences are also some problems that translators, readers and clients meet throughout their translation. Finally, the implications of these findings and suggestions for further research are also presented. The research result is hoped to be of some contribution to the translators and help them be more aware of difficulties as well as provide them with more techniques when translating English property insurance contracts into Vietnamese. In this sense, the findings are expected to bring a valuable benefit to students who studying insurance subject or staffs who working for non- life insurance companies or even clients how to translate an English property insurance contract into Vietnamese.